ROMANCE JEANE MARIE IN BEAUTY AND THE BEAST - Potabuga, Maryuni; Mogea, Tini; Sabudu, Delly (SoCul: International Journal of Research in Social Cultural Issues, 2022)
This research is mainly to find out the causes of conflict which is reflected in Brown’s novel entitled Beauty and the Beast through characters named Belle and the ugly prince. In conducting his research, the authors use qualitative research because the data collected is in the form of words, not numbers. An objective approach is used in analyzing the data. The results of this study found that there are very valuable lessons and knowledge, especially those related to the love relationship between two characters who come from different backgrounds. It is also stated that Belle was finally able to fall in love with the Ugly Prince even though she knew that the prince was not like humans in general. Although there are the differences between them, however in the end the two of them can be together forever because of the power of Belle’s love that can break the curse on the ugly prince. Keywords : Romance, Fairy Tale, conflic